Predicting iron deficiency and oxidative stress in Glycine max through Fourier transform infrared spectroscopy in a time-course experiment - Santos, Carla S.; Sousa, Clara; Bagheri, Maryam; Pinho, Simão; Vasconcelos, Marta W. (Plant and soil, 2024)
Aims The excessive use of fertilizers is a problem in current agricultural systems, and sustainable farming practices, including precision agriculture, demand the use of new technologies to manage plant stress at an early stage. To sustainably manage iron (Fe) fertilization in agricultural fields, it is urgent to develop early detection methods for Fe deficiency, and linked oxidative stress, in plant leaves. Herein, the potential of using Fourier Transform Infrared (FTIR) spectroscopy for Fe deficiency and oxidative stress detection in soybean plants was evaluated. Methods After a period of two weeks of hydroponic growth under optimum conditions, soybean plants were grown under Fe-sufficient (Fe+) and Fe-deficient (Fe–) hydroponic conditions for four weeks. Sampling occurred every week, infrared (IR) spectra were acquired and biological parameters (total chlorophyll, anthocyanins and carotenoids concentration, and ABTS and DPPH free radical scavenging ability), mineral concentrations, and the Fe-related genes’ expression - FRO2 - and IRT1 -like - were evaluated. Results Two weeks after imposing Fe deficiency, plants displayed decreased antioxidant activity, and increased expression levels of FRO2- and IRT1- like genes. Regarding the PLS models developed to estimate the biological parameters and mineral concentrations, satisfactory calibration models were globally obtained with R 2 C from 0.93 to 0.99. FTIR spectroscopy was also able to discriminate between Fe + and Fe– plants from an early stage of stress induction with 96.3% of correct assignments. Conclusion High reproducibility was observed among the different spectra of each sample and FTIR spectroscopy may be an early, non-invasive, cheap, and environmentally friendly technique for IDC management.